Electrooptic and Dielectric Studies in Cadmium Sulphide Nanorods/Ferroelectric Liquid Crystal Mixtures - Praveen Malik; Ashok Chaudhary; Rohit Mehra; K. K. Raina (Advances in Condensed Matter Physics)
We present the results based on the electrooptic and dielectric studies in cadmium sulphide (CdS) nanorods/ferroelectric liquid crystal mixtures. Doping of CdS nanorods increases the spontaneous polarization and response time, which due to large dipole-dipole interaction and increase in anchoring energies exists between nanorods and FLC molecules. Dielectric measurements revealed a decrease (~40% for 0.3% CdS in FLC) in permittivity and dielectric strength in doped sample cell than pure FLC mixture. A decrease in dc conductivity and relaxation frequency with doping concentration was also noticed. The preexponent factor and fractional exponent factor are found as predicated by existing theories.